Educational Case: Asthma: Clinical Features and Morphologic Findings - Maria Kamal MD; Mariam Ghafoor MD; Urooba Nadeem MD; Aliya N. Husain MD (Elsevier, 2020)
The following fictional case is intended as a learning tool within the Pathology Competencies for Medical Education (PCME), a set of national standards for teaching pathology. These are divided into three basic competencies: Disease Mechanisms and Processes, Organ System Pathology, and Diagnostic Medicine and Therapeutic Pathology. For additional information, and a full list of learning objectives for all three competencies, see http://journals.sagepub.com/doi/10.1177/2374289517715040 . 1